Prevalence rate of chloroquine resistance to plasmodium falciparum malaria among sudanese populations in malaria endemic areas in khartoum state and sennar state - Akasha, Ahmed Siddig; Badah, Hadia Ali (International Multidisciplinary Research Journal, 2012)
Objective: The study was carried out to assessment or to evaluate chloroquine Resistance of Plasmodium falciparum among Sudanese populations (10–85 years) ,malaria endemic area in Sennar region (Sennar state in South East Sudan) and Khartoum State (the capital). Design: The study was carried out on 190 samples of all of the study areas between March and December 2007, corresponding to the period of high malaria transmission. All samples were tested for chloroquine Resistance to Plasmodium falciparum by using in vitro micro tests. These study sites are located in an irrigated agricultural scheme, where transmission is seasonal. Setting: AL-Neelain University – College of Medical Laboratory Sciences – Sudan – Khartoum. Results: By using in vitro micro tests: In Sennar state the resistance to chloroquine was found to be 78.1% and about 21.9% were sensitive. Out of 105 patients only 23 patients(21.9%) were sensitive and 82 patients(78.1%) did not respond, 29 patients(27.6%), 19 patients (18.1%) and 34 patients (32.4%) of a total of 105 patients were early R1, RII and RIII levels of resistance respectively. In Khartoum state the the resistance to chloroquine was found to be 68.2% and about 31.8% were sensitive. Out of 85 patients only 27 patients (31.8%) were sensitive and 58 patients (68.2%) did not respond, 35 patients (41.2%) and 23 patients (27.1%) of a total of 85 patients were early R1 and RII levels of resistance respectively. Conclusions: By using in vitro micro tests: In Sennar state the resistance to chloroquine was found to be 78.1% and about 21.9% were sensitive while in Khartoum state the the resistance to chloroquine was found to be 68.2% and about 31.8% were sensitive.